A Green Alternative for Aryl Iodide Preparation from Aromatic Amines - Shahnavaz, Zohreh; Zaharani, Lia; Johan, Mohd R.; Khaligh, Nader Ghaffari (Current Organic Synthesis, 2020)
Background: In continuation of our previous work and the applications of saccharin, we encouraged to investigate the one-pot synthesis of the aryl iodides by the diazotization of the arene diazonium saccharin salts. Objective: Arene diazonium salts play an important role in organic synthesis as intermediate and a wide variety of aromatic compounds have been prepared using them. A serious drawback of arene diazonium salts is their instability in a dry state; therefore, they must be stored and handled carefully to avoid spontaneous explosion and other hazard events. Methods: The arene diazonium saccharin salts were prepared as active intermediates in situ through the reaction of various aryl amines with tert-butyl nitrite (TBN) in the presence of saccharin (Sac–H). Then, in situ obtained intermediates were used into the diazotization step without separation and purification in the current protocol. Results: A variety of aryl iodides were synthesized at a greener and low-cost method in the presence of TBN, Sac–H, glacial acetic acid, and TEAI. Conclusion: In summary, a telescopic reaction is developed for the synthesis of aryl iodides. The current methodology is safe, cost-effective, broad substrate scope, and metal-free. All used reagents are commercially available and inert to moisture and air. Also, the saccharine and tetraethylammonium cation could be partially recovered from the reaction residue, which reduces waste generation, energy consumption, raw material, and waste disposal costs.
Keywords: Green chemistry